2021
DOI: 10.1016/j.ijscr.2021.105830
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of a laryngeal leiomyosarcoma with a lymph node metastasis

Abstract: Highlights Leiomyosarcoma of the larynx a very rare malignancy. Leiomyosarcoma of the larynx may represent a serious diagnostic challenge. No therapeutic protocol has been established yet. Treatment modalities depends on size, location, extension of the tumor. The prognosis is conditioned by the quality of surgical excision and the occurrence of recurrence and metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…It may be an ulceroproliferative mass, a prolapsing exophytic tumor, a rounded mass with smooth surface, a pedunculated large glottic lesion, an irregular mass, a polypoid lesion, or a small, smooth submucosal lesion. Only two cases (3.3%) had neck lymph node metastasis 14,54 . The finding in the present case was an irregular mass at the anterior commissure covering the bilateral vocal cords and subglottic extension.…”
Section: Discussion/literature Reviewmentioning
confidence: 41%
See 4 more Smart Citations
“…It may be an ulceroproliferative mass, a prolapsing exophytic tumor, a rounded mass with smooth surface, a pedunculated large glottic lesion, an irregular mass, a polypoid lesion, or a small, smooth submucosal lesion. Only two cases (3.3%) had neck lymph node metastasis 14,54 . The finding in the present case was an irregular mass at the anterior commissure covering the bilateral vocal cords and subglottic extension.…”
Section: Discussion/literature Reviewmentioning
confidence: 41%
“…LLMS is uncommon; we identified 62 cases in the English‐language literature (Table 1). 1,3–55 Tangjaturonrasme found that the number of LLMS cases was increasing; four cases were reported from 1961 to 1970, compared to 21 cases from 2000 to 2010. This may be a result of advances in diagnostic techniques, including immunohistochemical techniques and electron microscopy 46 .…”
Section: Discussion/literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations